Remarkable Natural Material Surfaces and Their Engineering Potential - Lee, Michelle; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book explores a collection of natural surfaces, their scientific characteristics, and their unique engineering potential – demonstrating that engineering applications can be found in unexpected places. The surfaces covered range from botanical ones, like rice and lotus leaves, to insect surfaces, like butterfly and dragonfly wings. The variety of surfaces and numerous engineering potentials described show how biomimicry can be utilized to solve countless real-world problems.
Blood Clots and Vascular Networks: Self-Healing Materials -- Shark Skin: Taking a Bite Out of Bacteria -- Mother-of-Pearl: An Engineering Gem -- Diatoms: Glass Ornaments of the Earth’s Waters -- Lotus Leaves: Humble Beauties -- Dragonfly Wings: Special Structures for Aerial Acrobatics -- Moth Eyes: A New Vision for Light-Harnessing Efficiency -- Botanical Leaves: Groovy Terrain -- Snake Skin: Small Scales With a Large Scale Impact -- Gecko Pads: A Force to Be Reckoned With -- Butterfly Wings: Nature’s Fluttering Kaleidoscope -- Frog Skin: A Giant Leap for Engineering Applications -- Spider Silk: A Sticky Situation.
Keywords: Materials—Surfaces.; Thin films; Ecology .; Nature; Environment; Biochemical engineering; Nanochemistry; Surfaces and Interfaces, Thin Films; Ecology; Popular Science in Nature and Environment; Biochemical Engineering; Nanochemistry